p21 is Associated with the Proliferation and Apoptosis of Bone Marrow-derived Mesenchymal Stem Cells from Non-obese Diabetic Mice - Gu, Z.; Jiang, J.; Xia, Y.; Yue, X.; Yan, M.; Tao, T.; Cao, X.; Da, Z.; Liu, H.; Liu, H.; Miao, Y.; Li, L.; Wang, Z. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Recent studies have shown that autologous and allogeneic transplantation of the BM-MSCs had therapeutic effects on T1DM, whereas the BM-MSCs from the NOD mice itself did not have this therapeutic effect. We previously demonstrated that Bone Marrow (BM) -MSCs from the non-obese diabetic (NOD) mice had the abnormal migration and adhesion. So we hypothesized that the proliferation and apoptosis of the BM-MSCs from the NOD mice were dysregulated. Our team compared the proliferation and apoptosis between NOD mice and imprinting control region (ICR) mice. Then we assessed whether the NF-κB-p53/p21 pathway was involved in the process. The cell proliferation ability of the BM-MSCs from the NOD mice were significantly decreased, while the percent of apoptotic cells was increased compared to those from the ICR mice. The p21 expression was significantly increased in the NOD-MSCs. The p65 level was enhanced in the BM-MSCs from the NOD mice when compared to the ICR mice, coincided with the expression of p21. Expressions of p65 and p21 were significantly decreased in the BM-MSCs treated with p65 inhibitor. The knockdown p21 expression reversed the abnormal proliferation, colony formation and apoptosis of the BM-MSCs from the NOD mice. These data provide important preclinical references supporting the basis for further development of autologous MSC-based therapies for type1 diabetes mellitus (T1DM).
Keywords: diabetes; Graves’ disease; thyroid